The influence of trust in principals' mentoring experiences across different career phases - BAKİOĞLU, AYŞEN (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2010)
The purpose of this study is to examine the perceptions of primary school principals about the influence of 'trust' in their mentoring experiences. Both quantitative and qualitative methods were used in the study. The Primary School Principals' Mentoring Questionnaire previously developed by the researchers was applied to 1462 primary school principals. As a follow-up study, focus groups were carried out with 50 school administrators at various career phases in order to gather more in-depth data about the impact of 'trust' in the mentoring process. Results of the study showed that in different career phases, principals attached varied levels of importance to trust in the mentoring process.
Keywords: principals; mentoring; career phases; trust